Genetic predisposition to ductal carcinoma in situ of the breast. Issue 1 (December 2016) - Petridis, Christos; Brook, Mark; Shah, Vandna; Kohut, Kelly; Gorman, Patricia; Caneppele, Michele; Levi, Dina; Papouli, Efterpi; Orr, Nick; Cox, Angela; Cross, Simon; dos-Santos-Silva, Isabel; et al.
Abstract Background Ductal carcinomain situ (DCIS) is a non-invasive form of breast cancer. It is often associated with invasive ductal carcinoma (IDC), and is considered to be a non-obligate precursor of IDC. It is not clear to what extent these two forms of cancer share low-risk susceptibility loci, or whether there are differences in the strength of association for shared loci. Methods To identify genetic polymorphisms that predispose to DCIS, we pooled data from 38 studies comprising 5, 067 cases of DCIS, 24, 584 cases of IDC and 37, 467 controls, all genotyped using the iCOGS chip. Results Most (67 %) of the 76 known breast cancer predisposition loci showed an association with DCIS in the same direction as previously reported for invasive breast cancer. Case-only analysis showed no evidence for differences between associations for IDC and DCIS after considering multiple testing. Analysis by estrogen receptor (ER) status confirmed that loci associated with ER positive IDC were also associated with ER positive DCIS. Analysis of DCIS by grade suggested that two independent SNPs at 11q13.3 nearCCND1 were specific to low/intermediate grade DCIS (rs75915166, rs554219). These associations with grade remained after adjusting for ER status and were also found in IDC. We found no novel DCIS-specific loci at a genome wide significance level ofP  < 5.0x10-8 . Conclusion In conclusion, this study provides the strongest evidence to date of a shared genetic susceptibility for IDC and DCIS. Studies with larger numbers of DCIS are needed to determine if IDC or DCIS specific loci exist.